The Role of Carboxymethyl Cellulose (CMC) from Durian (Durio zibethinus) Rind in Enhancing Coconut Milk Stability Under Different Temperature Condition - Marina Wulandari Nasution; Juli Novita Sari (Green Publisher, 2025)
The influence of carboxymethyl cellulose (CMC) concentration derived from durian rind (Durio zibethinus) and temperature variations on coconut milk quality was investigated through three stages. The first stage involved the isolation of ?-cellulose from durian rind powder, which was analyzed using FTIR to confirm its identity as cellulose. In the second stage, a series of processes including alkalization with isopropanol and NaOH, carboxymethylation with NaMCA, and neutralization using 90% CH3COOH and ethanol were conducted, followed by purification with distilled water, centrifugation, and the addition of acetone. This resulted in CMC, which showed positive qualitative analysis and FTIR peaks similar to those of commercial CMC. The final stage focused on coconut milk production, where CMC was incorporated at concentrations ranging from 0.5% to 0.7%, and temperature variations were set at 16ºC, 25ºC, and 80ºC. The quality of the resulting coconut milk was assessed for stability, pH, viscosity, moisture content, protein content, fat content, free fatty acid content, and organoleptic properties. The optimal results were achieved with the addition of 0.7% CMC at 16ºC, yielding a stability percentage of 34.78% with a shelf life of 9.5 hours, a pH of 6.21, viscosity of 12.6138 x 10² cP, moisture content of 45.81%, protein content of 7.57%, fat content of 43.51%, and free fatty acid content of 1.402%. Organoleptic tests indicated that panelists favored the coconut milk with 0.7% CMC for its color and aroma. The quality analysis results for the coconut milk with CMC addition and temperature variations met the existing SNI standards.